A drug utilization study of oral anticoagulants in five representative cities of China between 2015 and 2019. (30th September 2021) - Gong, Xiaojiao; He, Qiuyi; Yan, Jiajia; Chen, Jie; Chen, Xiao; Huang, Min; Li, Jingjie; Chen, Pan
Abstract: What is known and objective: Oral anticoagulants (OACs), including warfarin and newer direct‐acting OACs (DOACs), have been used for decades to prevent thromboembolic diseases. A drug utilization study was performed to determine the prescribing patterns of OACs. Methods: Data were extracted from the Cooperation Project of Hospital Prescription Analysis in China. A total of 455, 490 prescription records from 43 tertiary hospitals in five cities of China (Beijing, Shanghai, Guangzhou, Hangzhou and Chengdu) were selected for inclusion. Quarterly trends of defined daily doses (DDDs) and defined daily dose cost (DDDC) from 1 January 2015 to 31 December 2019 were calculated. Results and discussion: Warfarin was the most widely used OAC with DDDs between 189, 982 and 176, 323 from the first quarter (Q1) of 2015 to the fourth quarter (Q4) of 2019, whereas the use of DOACs increased rapidly during this period. DDDs of rivaroxaban increased from 5409 in Q1 of 2015 to 125, 800 in Q4 of 2019, whereas the DDDC declined from 160.5 to 45.7. From Q1 of 2018, rivaroxaban became the most prescribed OAC, surpassing warfarin, in patients diagnosed with deep vein thrombosis. In addition, the DDDs of rivaroxaban exceeded those of warfarin in patients diagnosed with non‐valvular atrial fibrillation since the second quarter (Q2) of 2019. DDDs in outpatients and inpatients increased by 80.6% and 71.4%, respectively, and the DDDC for outpatients in Q4 of 2019 was 6.7‐fold higher than that in Q1 of 2015. Among patients of all ages, the DDDs in elderly patients increased from 36.8% in Q1 of 2015 to 59.4% in Q4 of 2019. Moreover, the departments of cardiology and cardiothoracic surgery prescribed the majority of the OACs. What is new and conclusion: In this study, we describe OAC prescription patterns in China. DOACs, especially rivaroxaban, contribute to the continuous increase in the use of OACs. In the investigated population of China, outpatients and elderly patients were observed to be administered the highest proportion of DOACs. Abstract : DOACs, especially rivaroxaban, contribute to the continuous increase in the use of OACs in China. Outpatients and elderly patients were administered the highest proportion of DOACs.